A pure nongestational choriocarcinoma of the ovary diagnosed with short tandem repeat analysis: case report and review of the literature. Issue 1 (1st January 2007) - Yamamoto, E.; Ino, K.; Yamamoto, T.; Sumigama, S.; Nawa, A.; Nomura, S.; Kikkawa, F.
Abstract : Nongestational pure choriocarcinoma of the ovary is a very rare germ cell tumor. Except in women before menarche, determination of the origin is very difficult without genetic analysis. We present a pure nongestational choriocarcinoma arising in the left ovary of a 19-year-old woman. Following surgery, pathologic findings of the tumor demonstrated pure choriocarcinoma without combination of other germ cell tumor elements. We confirmed its nongestational origin by DNA polymorphism analysis at 15 short tandem repeat loci. Multiple courses of chemotherapy with methotrexate, etoposide, and actinomycin-D were effective for this case. DNA polymorphism analysis is useful to determine genetic origin in pure choriocarcinoma of the ovary